Serous Effusions Diagnostic Accuracy for Hematopoietic Malignancies: A Cyto-Histological Correlation - Li, Jinnan; Zhao, Sha; Zhang, Wenyan; Jiang, Yong; Zhu, Xianglan; Den, Xueqin; Liu, Weiping; Su, Xueying (Frontiers in Medicine, 2020)
Background: The aim of this study was to establish the liability of cytological diagnostic and, along with ancillary techniques, to sub-classify hematopoietic malignancies in serous effusions. Methods: We retrospectively reviewed the serous effusions of hematopoietic malignancies over an 11-year period, along with ancillary studies, clinical and histological data. We compared cytological along with histological diagnosis to evaluate the value of cytology itself. Furthermore, the discrepant cases were reviewed. Results: In this study, a total of 242 cases were identified as hematopoietic malignancies. Ancillary technologies were performed: in 24 cases FCM, 242 cases ICC, 35 cases ISH, 81 cases PCR and 10 cases FISH. Cyto-histological correlation was available for 122 cases. The subtyping of hematopoietic malignancies was achieved using cytological material in 65/122 cases (53.3%). Of the 65 cases, T-Acute lymphoblastic leukemia/lymphoma (22.1%) was the leading subtype, followed by Burkitt lymphoma (5.7%), plasmacytoma (5.7%). Cyto-histological correlation showed a 100% concordant rate of diagnosis for hematopoietic malignancies and a high degree of agreement on sub-classification (51.6%). In this regard, T-acute lymphoblastic leukemia/lymphoma, plasmacytoma, extranodal NK/T-cell lymphoma, nasal type, anaplastic large cell lymphoma, myeloid sarcoma and follicular lymphoma showed the highest degree of agreement (100%). The sub-classification on cytology was achieved in 53 out of the remaining 120 cases without histological diagnosis (44.2%). T-acute lymphoblastic leukemia/lymphoma (20.8%) was again the most frequently encountered subtype, followed by plasmacytoma (5.8%) and Burkitt lymphoma (4.2%). Conclusions: This large series study provided evidence that combining cytology and ancillary studies enabled the accurate serous effusions cytological diagnoses and subsequent sub-classification for the described malignancies.